SUCCESS AND FAILURE OF HERO AND VILLAIN AS THE STORYTELLING IN INTERACTIONAL AND INSTITUTIONAL CONTEXT: AN ANALYSIS OF PAKISTANI DIPLOMATIC CYPHER UNDER VLADIMIR PROP'S MORPHOLOGY OF FOLK TALE (1968) - Zahra Maqsood; Dr. Muhammad Ilyas Mahmood; Wasim Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study is conducted to understand the morphology of the Folk Tale that existed in the Pakistan Diplomatic Cypher (March 07, 2022). The study is descriptive and based on elements of the Folk Tale model of Vladimir Prop's Morphology (1968) that existed in the Pakistani Diplomatic Cypher. The Folk Tale model of Vladimir Prop's Morphology (1968) consists of the 31 story elements that are critically explored in the Cypher. The study found that the Hero Imran Khan tried to defend its national foreign policy before the US, but he could not save the regime and could not firmly reach the Wedding (Happiness). On the other hand, the US, as the Hero, succeeded in catching the targets of its foreign policy through Regime Change in Pakistan and met the Wedding (became happy). Imran Khan was punished as the villain of the US, while the US, as the villain against Imran Khan, could not be punished.